2021
DOI: 10.3390/su13137082
|View full text |Cite
|
Sign up to set email alerts
|

Digital Innovation in Times of Crisis: How Mashups Improve Quality of Education

Abstract: Innovation is a crucial force underlying the organizational and societal ability to survive and thrive in crisis times, especially in education. However, not all challenges require creating novel solutions; occasionally, combining pre-existing solutions—an approach known as the mashup methodology—can provide equal benefit. Nevertheless, this approach appears to be relatively unknown. In the current case study, we provide an example of using a mashup of technologies to solve the challenge of running a remote vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 78 publications
0
8
0
Order By: Relevance
“…When students perceive online hackathons as useful and easy to use and have a high level of SE in using the platform, they are more likely to develop a positive attitude towards using them and have a stronger intention to use them for learning. Furthermore, studies have found that students' BI to use hackathons is positively related to their actual use of the platform (Maaravi & Heller, 2021;Oyetade et al, 2023). This suggests that BI is an important predictor of students' actual engagement with online hackathons and their use as a mode of learning.…”
Section: Behavioral Intentionmentioning
confidence: 99%
See 1 more Smart Citation
“…When students perceive online hackathons as useful and easy to use and have a high level of SE in using the platform, they are more likely to develop a positive attitude towards using them and have a stronger intention to use them for learning. Furthermore, studies have found that students' BI to use hackathons is positively related to their actual use of the platform (Maaravi & Heller, 2021;Oyetade et al, 2023). This suggests that BI is an important predictor of students' actual engagement with online hackathons and their use as a mode of learning.…”
Section: Behavioral Intentionmentioning
confidence: 99%
“…To assess this, you could ask students questions such as "How useful do you think participating in the online hackathon will be for improving your coding skills or help you achieve your career goals?" Online hackathons have gained popularity in recent years as a means of providing students with hands-on experience in realworld problem-solving with PU of hackathons found to have a big impact on whether or not students intend to employ this form of learning to accomplish their learning objectives (Maaravi & Heller, 2021;Oyetade et al, 2022). Furthermore, PU of online hackathon can impact students' engagement and motivation to participate in these events (Lee & Mendlinger, 2011;Oyetade et al, 2023).…”
Section: Perceived Usefulnessmentioning
confidence: 99%
“…Digital education, which often implies the use of a remote form of training, is criticised in the existing works of Maaravi and Heller (2021), Rodríguez-Abitia et al (2020), and Saltos-Rivas et al (2021, because it may reduce the quality of education. Contrary to this, Gunathilaka et al (2022), Kasımoğlu et al (2022), andLi et al (2022) note the important contribution of digital education to the support for the normal functioning of the educational system under the conditions of lockdowns that took place during the COVID-19 pandemic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Vocational education, as a type of education, is an important part of the national education system and human resources development, shouldering the important responsibility of cultivating diversified talents, inheriting technical skills, and promoting employment and entrepreneurship [1]. Vocational education and the established paradigm have undergone fundamental changes due to digital technology [2][3]. The existence of vocational education, system structure, parenting mode, and governance have been reconfigured by digital technology.…”
Section: Introductionmentioning
confidence: 99%